The geopolitics of trillion US oil & gas rents - Verbruggen, Aviel (International Journal of Sustainable Energy Planning and Management, 2022)
Physical oil and gas abundance, turned in market scarcity, do prices of oil and gas spike and cashed rents mount. For the years 1970-2020, the rents from crude oil and natural gas sales are expressed in US-2020, revealing the magnitude and volatility of the money flows. Peak rents coincide with turmoil implying particular oil & gas exporting countries. Oil & gas geopolitics metamorphosed from conquering oil deposits to precluding oil & gas exports by ‘hostile’ nations. Such preclusions turn physical abundance in market scarcity, boosting oil & gas prices and rents (also called royalties, windfall, excess profits). Rent skimming is also a part of the 2022 Ukraine war. Climate change mitigation intensifies geopolitical efforts to curtail the exports of ‘hostile’ nations.